Posing the APC/C E3 ubiquitin ligase to orchestrate cell division - Watson, Edmond R. (Trends Cell Biol, 2018)
The APC/C E3 ligase controls mitosis and non-mitotic pathways through interactions with proteins that coordinate ubiquitylation. Since the discovery that the catalytic subunits of APC/C are conformationally-dynamic “cullin” and “RING” proteins, many unexpected, intricate regulatory mechanisms have emerged. Here we review structural knowledge of this regulation, focusing on: (1) coactivators, E2 ubiquitin conjugating enzymes, and inhibitors engage or influence multiple sites on APC/C including the cullin-RING catalytic core; and (2) the outcomes of these interactions rely on mobility of coactivators and cullin-RING domains, which permits distinct conformations specifying different functions. Thus, APC/C is not simply an interaction hub, but is instead a dynamic, multifunctional molecular machine whose structure is remodeled by binding partners to achieve temporal ubiquitylation regulating cell division.